Ceramic Veneers. Biomechanical Principles Applied to the Treatment of Lateral Conoid Incisors. Clinical Case Report - Ramírez Barrantes, Juan Carlos (2020)
Ceramic veneers are considered viable alternatives compared to classic invasive procedures applied in restorative treatments. Adhesive bonding techniques combined with restorative materials that mimic the natural color of the tooth are part of one of the greatest achievements in modern aesthetic dentistry. Ceramic veneers structurally made with lithium disilicate materials are frequently selected to restore and stabilize the biomechanics of the tooth in cases with dental malformations, such as conoid teeth. This article explains the basic principles applied to the design of ceramic veneers, with copings in lithium disilicate and covered with feldspathic ceramic. Moreover, the long-term prognosis of ceramic veneers based on scientific evidence.